The nature of elastoplastic transition in low-carbon steel samples with and without welds; IOP Conference Series: Materials Science and Engineering; Vol. 286 : Modern Technologies and Materials of New Generations (MTMNG-2017) - Danilova L. V. (2018, 2018)
Title screen